2020
DOI: 10.3390/horticulturae6040105
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Postharvest Storage and Processing Techniques on Antioxidant and Nutraceutical Properties of Rubus idaeus L.: A Mini-Review

Abstract: The growth of agricultural mechanization has promoted an increase in raspberry production, and for this reason, the best postharvest storage and processing techniques capable of maintaining the health beneficial properties of these perishable berry fruits have been widely studied. Indeed, raspberries are a rich source of bioactive chemical compounds (e.g., ellagitannins, anthocyanins, and ascorbic acid), but these can be altered by postharvest storage and processing techniques before consumption. Although ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…As a perishable soft fruit, raspberries are often processed and consumed as wines, juices, and jams [ 5 ]. However, processing techniques (e.g., thermal processing) may alter the bioactive compounds in raspberries, leading to a decrease in the health-promoting properties of the end products [ 6 ]. Thus, it is a challenge for the food industry to find alternative ways to preserve the nutritional and nutraceutical properties of fruit products.…”
Section: Introductionmentioning
confidence: 99%
“…As a perishable soft fruit, raspberries are often processed and consumed as wines, juices, and jams [ 5 ]. However, processing techniques (e.g., thermal processing) may alter the bioactive compounds in raspberries, leading to a decrease in the health-promoting properties of the end products [ 6 ]. Thus, it is a challenge for the food industry to find alternative ways to preserve the nutritional and nutraceutical properties of fruit products.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenolic compounds belong to the group of secondary metabolites responsible for defense mechanisms in plants, primarily towards microbiological infections, including viral infections. The contents of these compounds in fruits depend on various factors, including the fruit species, variety, maturity stage, soil substrate, plant health status, and agricultural practices [37][38][39]. In this research, the influence of the cultivar was excluded, since only the 'Willamette' cultivar was utilized for the analyses.…”
Section: Influence Of Rlbv Infection Harvest Year and Locality On Pol...mentioning
confidence: 99%
“…The fruits are also preserved by various drying techniques such as hot air-drying, freeze-drying, microwave-drying, and hot pumpdrying. The advantages and disadvantages of these methods are discussed in the review paper prepared by Piccolo et al (2020). The authors concluded that the freeze-drying method is most likely the best choice for the preservation of bioactive compounds.…”
Section: Raspberrymentioning
confidence: 99%